Rethinking the Silk Road
IX, 287 p.
Keywords: "Mayer provides a compelling rationale to focusing on China’s grand ambitions in the context of China’s external relations. It is a rare combination of nuanced historical narratives with detailed empirical studies and comparative frameworks. This brilliant and thoughtful book tackles the most important question facing the world in the 21st century—China’s future grand strategy. It should be a must-read for serious scholars and policy makers around the world who are interested in or concerned about China’s rise." —Dingding Chen, Professor of International Relations, Jinan University, Guangzhou, China "China’s belt and road initiative makes a turning point in China’s search for a grand strategic narrative and in the debates about China’s rise. This excellent collection of papers combines a series of in-depth empirical studies from the perspective of China’s relationships with key countries and regions, with systematic exploration of theoretical frameworks for understanding the initiative. It will be a valuable resource for practitioners and scholars alike." —Tim Summers, Chatham House, Asia Program Focused on the "Belt and Road Initiative", this book discusses China’s opportunities to translate economic leverage into political outcomes. The central question is how China’s expanding economic influence will transform the Eurasian political landscape. Proposed in late 2013 by President Xi Jinping, the Belt and Road is the most ambitious foreign policy approach adopted thus far and represents the culmination of China’s search for a grand strategic narrative. Comparative methods and diverse conceptual frameworks are applied to contextualize and explore the political, economic, and cultural ramifications of the Belt and Road in order to shed light on its transformative significance, risks and opportunities. Maximilian Mayer is a research professor at the German Studies Center of Tongji University,China. He is co-editor of the two-volume The Global Politics of Science and Technology and Art and Sovereignty in Global Politics. His research interests include the global politics of technoscience and innovation, China’s foreign and energy policy, global climate politics, and International Relations theories.